INFRARED PHOTOMETRY OF SAKURAI’S OBJECT (V4334 Sgr) IN 1996-2000 - Tatarnikov, A. M.; Shenavrin, V. I.; Whitelock, P. A.; Feast, M. W.; Yudin, B. F. (Одеські астрономічні публікації, 2017)
The results of the photometric observations of V4334 Sgr and characteristics of its evolution after outburst are presented.